ISSUES IN THE MARKETING OF LIBRARY, INFORMATION PRODUCTS AND SERVICES AT UNIZIK LIBRARY (NAU Journal of Library and Information Science, 2018)
The paper discussed issues surrounding the marketing of library and information services in Festus Aghagbo Nwako Library. It highlighted the concept of marketing library services as well as strategies that will enhance library operations both in the traditional library setting and in the digital environment. It recommended different information literacy skills such as knowledge acquisition, use of library oriented social media, talk shows, institution of annual library week,webnar among others.
Keywords: Marketing Information Services; Traditional Library; Information Literacy; Social Media Marketing; Festus Aghagbo Nwako Library